2018
DOI: 10.18502/ijhoscr.v12i4.110
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Oral Ginseng on the Cancer-Related Fatigue and Quality of Life in Patients with Non-Metastatic Cancer

Abstract: Background: Cancer affects the physical, psychological, and social aspects of the patients’ life. Cancer-related fatigue (CRF) is the most common and severe condition among cancer patients. Ginseng has long been used as an efficient treatment for CRF and improvement of quality of life (QOL). The present study aims to assess the efficacy of Panax Ginseng (PG) in reducing CRF in patients with non-metastatic cancer. In addition, the safety of the medication is evaluated. Materials and Methods: This was a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…A majority of participants were reported to be on active cancer treatment either in the form of systemic therapy or radiation, although Yennurajalingam and colleagues (2017) did not report this data. Duration of treatment with ginseng ranged from 29 to 56 days ( Barton et al, 2010 , 2013 ; Chang et al, 2018 ; Pourmohamadi et al, 2018 ; Yennurajalingam et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…A majority of participants were reported to be on active cancer treatment either in the form of systemic therapy or radiation, although Yennurajalingam and colleagues (2017) did not report this data. Duration of treatment with ginseng ranged from 29 to 56 days ( Barton et al, 2010 , 2013 ; Chang et al, 2018 ; Pourmohamadi et al, 2018 ; Yennurajalingam et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there was no significant improvement of CRF in advanced cancer patients, the symptoms of CRF (pain, appetite and quality of life) can be markedly improved in the patients suffering from nonmetastatic colon cancer after ingesting P. ginseng for 30 days [ 104 ]. Particularly, chemotherapy and radiotherapy were major factors that can develop severe fatigue [ 118 , 119 ].…”
Section: Anti-fatigue Effect In the Clinical Settingmentioning
confidence: 99%
“…For example, red ginseng can significantly improve mood, relations with others, walking ability and enjoyment of life in colorectal cancer patients with chemotherapy [ 105 ]. Oral ginseng also can improve quality of life, such as muscular pain, degree of happiness, appetite and sleep quality, as well as mood condition in nonmetastatic cancer patients [ 104 ]. In general, P. ginseng treatment can improve the quality of life in patients with various diseases, which was better in long-term treatment.…”
Section: Anti-fatigue Effect In the Clinical Settingmentioning
confidence: 99%
“…Among the various herbs proposed to improve cancer treatment, ginseng has attracted the most interest worldwide. Numerous studies have shown that ginseng is able to treat cancer-related symptoms and has the potential to improve the quality of life of patients with cancer 10-12. Among the various components of ginseng, ginsenosides have been identified as the main active components and have been investigated extensively 13.…”
Section: Introductionmentioning
confidence: 99%